Evaluation against sheath blight disease of maize under natural conditions - and N.P. SINGH, SUBRATA BISWAS*, K. CHATTOPADHYAY (Indian Phytopathology, 2007)
Sheath blight disease caused by Rhizoctonia solani was studied in 38 maize genotypes, including 6 popular varieties and 12 crossbreeds, at the research farm, NEH Region, Tripura Centre during the period of 2002 to 2005 for evaluating resistance. Of the popular varieties tested, 'Prakash' was found as the most tolerant to the disease while 'Jhum Red' was the most susceptible. The tolerance (resistance) to sheath blight of 'Prakash' was able to combine in the crossbreeds developed by crossing the variety with others. Out of 20 genotypes of NEH region, four, viz., DRLT-180 IC324207,G-RS-7, RKU-193 IC309233and MZ-80 IC339731, were identified as resistant to sheath blight disease, which suggesting their possible utilization in breeding work for incorporating resistance into the popular high yielding varieties.